The life course of impulsive males from childhood to adulthood - Farrington, David P.; Aguilar Carceles, Marta Maria (Journal of Criminal Psychology, 2023)
Purpose: This paper aims to advance knowledge about the life course of impulsive males from childhood to adulthood, based on data collected in the Cambridge Study in Delinquent Development (CSDD) from age 8 to 65 and to investigate which factors are related to impulsiveness at different ages. Design/methodology/approach: The CSDD is a prospective longitudinal survey of 411 London males first studied in 1961–1962 at age eight. The males have been assessed face-to-face nine times from age 8 to 48. A total of 77 impulsive boys and 334 non-impulsive boys were identified at ages 8–10 using three measures of impulsiveness: daring/risk-taking (rated by parents and peers), psychomotor clumsiness/impulsivity (based on psychomotor tests of the boys) and poor concentration/restless in class (rated by teachers). Findings: Parental, family, socio-economic, academic attainment and behavioural factors in childhood were the most significant variables that were related to impulsiveness at ages 8–10. Impulsive males had low IQ, truancy, high daring and a high antisocial personality score at ages 12–14. No exams passed, and a low socio-economic status job were especially significant at ages 16–18, while poor employment, convictions (especially for violence), anti-establishment attitudes and an unsuccessful life were especially characteristic of impulsive males in adulthood (ages 32–48). Practical implications: Child skills training programmes are needed to reduce childhood impulsiveness. Originality/value: To the best of the authors’ knowledge, this is the first-ever publication that documents the life course of impulsive males from childhood to late adulthood.
Keywords: antisocial behaviour; childhood to adulthood; impulsiveness; longitudinal study; offending; risk factors; Scopus; Emerging